Blockchain-based diploma information system development - Heru Saputra; Bebby Ilham Aresta; Tri A Sundara; Ilfa Stephane; Lakry Maltaf (invotek, 2021)
A diploma is a document of recognition of learning achievement from a level of education obtained after completing the study period after passing the final exam. The importance of the certificates' existence for working purposes has resulted in the proliferation of making and using fake certificates for various purposes such as applying for jobs, fulfilling the requirements to become members of the legislature, etc. The Diploma Information System using blockchain-based distributed computing can be one way to maintain the diploma's authenticity and validity. This study uses the waterfall method with several applications, ethereum remix ideas, ganache, and metamask, aiming to develop blockchain-based diploma information on STMIK Indonesia Padang by utilizing blockchain technology.